Innowacje w strategii rozwoju Polski w drugim okresie programowania 2007-2013 - Rymarczyk, Jan (Innovations in Polish Development Strategy in Second Programming Period 2007-2013, 2008)
The level of innovations in Polish economy is very low. The synthetic measure of it is the outlays forR&D, which in Poland are 0,57% GPD while in the European Union almost 1.9%. In connection with it Poland has decided that according to recommendation of the Lisbon Agenda a considerable part of the financial aid, which Poland will receive from the EU in 2007-2013 will spend on the innovations first of all within the Operating Program Innovative Economy and 10 Regional Operating Programs.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 12, s. 173-184